Jasper Eng's answer to CWX's Malaysia question.
done
{{ upvoteCount }} Upvotes
clear
{{ downvoteCount * -1 }} Downvotes
1) if a is a root:
-a is also a root
Sum of roots:
-p-4 = a - a = 0
P = 4
Product of roots:
-p^2 = -a^2
-a^2 = - (4)^2 = -16 //
2) if equation has 2 equal roots:
Discriminant = 0
D = B^2 - 4AC
= (-9n)^2 - 4(m) (m) = 0
81n^2 - 4m^2 = 0
81n^2 = 4m^2
m^2 / n^2 = 81/4
(m/n)^2 = 81/4
:.m/n = square root(81/4)
= 9/2
:. m:n = 9:2 //
-a is also a root
Sum of roots:
-p-4 = a - a = 0
P = 4
Product of roots:
-p^2 = -a^2
-a^2 = - (4)^2 = -16 //
2) if equation has 2 equal roots:
Discriminant = 0
D = B^2 - 4AC
= (-9n)^2 - 4(m) (m) = 0
81n^2 - 4m^2 = 0
81n^2 = 4m^2
m^2 / n^2 = 81/4
(m/n)^2 = 81/4
:.m/n = square root(81/4)
= 9/2
:. m:n = 9:2 //
Date Posted:
3 years ago
ThankQ!